STRATEGI KEPEMIMPINAN PROFETIK DALAM MENGELOLA LEMBAGA PENDIDIKAN ISLAM DI MASA KRISIS - Dicky Artanto; Zainal Arifin; Diningrum Citraningsih (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2022)
In times of crisis the COVID-19 pandemic requires that all aspects of life undergo changes from conventionality becomes digital, and the impact is no exception for institutions Islamic education. This article examines the prophetic leadership strategies in Islamic educational institutions in the era of change due to the COVID-19 Pandemic in relation to the way the institution can survive various changes that occur, under the control of a leader. This research method uses field research, namely field research at STAIT BIAS Yogyakarta with Interviewed several respondents, field observations, and documentation analysis using data in the form of doumen and related data sources contained in islamic educational institutions. Data analysis using miles and huberman methods is by data collection, data reduction, presentation of data, and withdrawal of conclusions or verification of data. Based on the results of research that the prophetic leadership strategy in managing the Islamic education institution STAIT BIAS Yogyakarta during the crisis due to the COVID-9 pandemic is the leadership is trying to provide a decision that is important for all members of the academic community. As for example the policy of sidiq aspect , that the value of honesty built is in terms of presence, at STAIT BIAS Yogyakarta does not use finger print but is written manual in the journal of the presence of both lecturers and employees. The trust or amanah aspect, STAIT BIAS Yogyakarta is accustomed to starting to build that value from a small thing, namely when the meeting is all obliged to record the results of the verdict agreed in the meeting. Its function as a reminder so that the decision can be realized as well as possible. Aspect tablig, the leaders in setting policy decisions not only look at the rules of the Foundation, but consider from the aspect of regulations that develop in the community with the principle of maintaining benefits, for example in the determination of Work From Home (WFH). The fatanah well,intelligence here is how the leader is able to present as a problem solver and provide the best solution. At STAIT BIAS Yogyakarta in the face of pandemic crisis in decision making always considers the aspects of the safety of the academic community and the welfare in general. So that the policies rolled out can provide solutions to what is a common need. The implication of this research has been done as an improvement in scientific characteristics about prophetic leadership related to managing Islamic educational institutions in times of crisis due to the COVID-19 pandemic.